1985
DOI: 10.1515/zna-1985-0904
|View full text |Cite
|
Sign up to set email alerts
|

New Approach, Taking into Account Elastic and Inelastic Processes, for Transport Properties of a two Temperature Plasma

Abstract: We have developed a modified Chapman-Enskog method for a two-temperature partially ionized plasma: electron temperature (Te) and heavy particles temperature (Th). We introduce a new definition of the diffusion forces and then calculate the reactive thermal conductivity λR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
10
0
5
Order By: Relevance
“…Whereas the community agrees the calculation of the thermodynamic properties, translation thermal conductivities of electrons and heavy particles, viscosity and electrical conductivity, there is no consensus for the calculation of the reactive thermal conductivity. The theory of Hirschfelder et al [12] or Bonnefoi et al [48,49] consider separately the electrons and the heavy particles whereas the theory of Rat showed that these two theories did not consider correctly not only the diffusion in 2T plasmas but also the coupling between electrons and heavy particles. The Rat's theory leads to new definitions of collision integrals, transport coefficients and consequently new terms in energy fluxes.…”
Section: Plasma In Nlte And/or Nlce Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the community agrees the calculation of the thermodynamic properties, translation thermal conductivities of electrons and heavy particles, viscosity and electrical conductivity, there is no consensus for the calculation of the reactive thermal conductivity. The theory of Hirschfelder et al [12] or Bonnefoi et al [48,49] consider separately the electrons and the heavy particles whereas the theory of Rat showed that these two theories did not consider correctly not only the diffusion in 2T plasmas but also the coupling between electrons and heavy particles. The Rat's theory leads to new definitions of collision integrals, transport coefficients and consequently new terms in energy fluxes.…”
Section: Plasma In Nlte And/or Nlce Conditionsmentioning
confidence: 99%
“…Ghorui et al [45,46] in 2008 and Colombo et al in 2009 [43, 44] showed in their works that the method of Devoto is sufficient to determine the transport properties (electrical conductivity, thermal conductivity and viscosity) in 2T assumption only if diffusion coefficients defined by Ramshaw were used. From the last works published on 2T-properties for several gases applied in various applications (Bonnefoi et al [48,49] for Ar-H, Mexmain [50] for Ar-O, McCourt [51] for polyatomic mixtures, Aubreton et al [52][53][54] for Ar-O2, Ar-He or pure N2, Capitelli et al [55,56] with a "State-to-State" model applied for pure N 2 and H 2 plasmas, Guo et al [57], Zhang et al [58] and Yang et al [59] on helium, argon and SF 6 -N 2 mixtures) we can consider as accepted that the translation and internal thermal conductivities of heavy particles and the viscosity can be calculated at T h , the translation thermal conductivity of electrons and the electrical conductivity at T e . The figure 6 compare these coefficients obtained for the cases 1 and 2, the LMA and CR/CK methods, in the case of pure SF 6 at 1 bar and θ = 5.…”
Section: Plasma In Nlte And/or Nlce Conditionsmentioning
confidence: 99%
“…Z PROPRIÉTÉS DE TRANSPORT. -Nous ne rappelons pas le formalisme permettant le calcul des propriétés de transport, nous nous référons aux articles [9,10]. Pour les intégrales de diffusion (1 = 1) de la collision 0-0+ nous notons (1) celles obtenues à Fig.…”
Section: Composition Propriétés Thermodynamiques -unclassified
“…Il y a alors redistribution des vitesses pour ces deux sous-ensembles de particules, au voisinage de deux maxwelliennes, l'une à la température Te pour les électrons et l'autre à la température Th pour les particules lourdes. Dans deux précédents articles nous avons adopté la théorie cinétique de Chapman-Enskog à un plasma à deux températures et nous en avons déduit les expressions des coefficients de transport jusqu'à la quatrième approximation pour les processus élastiques [9] et à la première approximation pour les processus inélastiques [10].…”
unclassified
See 1 more Smart Citation